Lubricated Conditions Imposed on Coating Multi-layer on Wear Resistance Under Cr2O3 Effect - Al-Samarai, Riyadh A.; Al-Douri, Yarub (Associacao Brasileira de Metalurgia e Materiais (ABM); Associacao Brasileira de Ceramica (ABC); Associacao Brasileira de Polimeros (ABPol), 2018)
Lubricated pin-on-disk sliding wear tests were performed on applied to Al-0.1Mg-0.35Ni-Si Alloy by using the spray coating method has been investigated. Different loads were 5, 10, and 15 N at a sliding velocity, 1.32 m/s at room temperature and 60% relative humidity. The surfaces were analyzed by using X-ray diffraction the residual (XRD), energy dispersive (EDS), scanning of (SEM) and (AFM), respectively. The results have showed that the thickness of Cr 2 O 3 coating was significantly related under the identical cold spray condition. These methods have contributed much of the understanding of quality and properties of surfaces. The (Cr 2 O 3 ) coating has great potential as a wear-resistant. The hardness increased from 102 ± 5 HV to 116.4 ± 2.5 HV at coating thickness 45 µm and friction coefficient reduced from 0.29 to 0.24; and the wear rate was about 2.11X10 -13 m 3 N -1 m -1 while hardness was increased from 102 ± 5 HV to 108 ± 3.5 HV at coating thickness 15 µm. The friction reduced from 0.31 to 0.29 at same coating thickness alloys, and the wear rate was about 2.73X10 -13 m 3 N -1 m -1 . The tribological properties of Cr 2 O 3 coating have exhibited low friction and beneficial to improve the adhesion which was clear on worn surfaces of Cr 2 O 3 coating. Crack, powder flocculation and powder formation are caused by the wear mode of the surface. Brittle fracture was found; while, adhesion and oxidation are the main mechanism of wear during the test.